Strategi Konseling Individual Untuk Mengatasi Stres Akademik Pada Mahasiswa - Anwar Fuadi; Fitriana Suprapti; Iswahyu Pranawukir; Taupiq Taupiq (Journal on Education, 2023)
Academic stress is a significant issue experienced by students at various levels of education. Academic stress can have a negative impact on students' well-being and their academic performance. Individual counseling has been recognized as an effective approach in helping students cope with academic stress. Therefore, this desk research aims to analyze, synthesize, and evaluate relevant sources on individual counseling strategies to address academic stress in university students. The desk research method was conducted by collecting relevant literature sources through academic databases, scientific journals, and books related to the research topic. The selected sources must have good methodological strength and be relevant to individual counseling strategies to overcome academic stress in college students. Afterwards, the sources were critically analyzed to identify the main findings and successful individual counseling strategies in reducing academic stress in university students. The results of the analysis and synthesis of the literature sources show that there are several individual counseling strategies that are effective in addressing academic stress in university students. These strategies include relaxation techniques, time management, study skills development, social support, self-regulation, and adaptive mindset development. Previous research has also shown that individual counseling conducted by trained and experienced counselors has a positive impact in reducing academic stress and improving student well-being. This study has important implications for counseling practitioners and researchers in the field of education. By understanding effective individual counseling strategies, counseling practitioners can develop appropriate and scalable interventions to help college students cope with academic stress. In addition, this study also identified research gaps that could be an opportunity for further research in this area.